Marine fatty acids aggravate hepatotoxicity of α-HBCD in juvenile female BALB/c mice. (November 2016) - Bernhard, Annette; Berntssen, Marc H.G.; Lundebye, Anne-Katrine; Røyneberg Alvheim, Anita; Secher Myrmel, Lene; Fjære, Even; Torstensen, Bente E.; Kristiansen, Karsten; Madsen, Lise; Brattelid, Trond; Rasinger, Josef D.
Abstract: Oily fish, a source of long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFAs), may contain persistent organic pollutants (POPs), including α-hexabromocyclododecane (α-HBCD). In experimental studies, marine LC n-3 PUFAs ameliorate fatty liver development while HBCD exposure was found to cause liver fatty acid (FA) changes. The present study investigated interactions of FAs and α-HBCD in juvenile female BALB/c mice using a factorial design. Mice (n = 48) were exposed for 28 days to a low (100 μg*kg body weight (BW) −1 *day −1 ) or high dose (100 mg*kg BW −1 *day −1 ) of α-HBCD in diets with or without LC n-3 PUFAs. High dose α-HBCD affected whole body lipid metabolism leading to changes in body weight and composition, and pathological changes in hepatic histology, which surprisingly were aggravated by dietary LC n-3 PUFAs. Hepatic FA profiling and gene expression analysis indicated that the dietary modulation of the hepatotoxic response to the high dose of α-HBCD was associated with differential effects on FA β-oxidation. Our results suggest that in a juvenile mouse model, marine FAs accentuate hepatotoxic effects of high dose α-HBCD. This highlights that the background diet is a critical variable in the risk assessment of POPs and warrants further investigation of dietary mediated toxicity of food contaminants. Highlights: Dietary α-HBCD exposure affected lipid metabolism in juvenile female BALB/c mice. At a high exposure level, dietary α-HBCD affected growth and body composition, and caused severe aberrations in the liver. Hepatic fatty acid composition suggested an effect of α-HBCD exposure on the function of fatty acid metabolizing enzymes. The impact of α-HBCD exposure on lipid metabolism was dependent on the dietary fatty acid composition. Interaction with marine lipids should be considered in future risk-benefit assessments of POPs from oily fish consumption.